Fetal yawning and mouth openings: Frequency, developmental trends, and association with birth weight - Damiano Menin; Paola Veronese; Maria Teresa Gervasi; Harriet Oster; Marco Dondi (PLoS ONE, 2026)
During the last 15 years, the brain cooling hypothesis has shown unparalleled explanatory and predictive power among the several attempts aimed at elucidating the phylogenetic origins of yawning. However, some blind spots remain which are not directly accounted for by this theoretical explanation, including the presence of yawning in human fetuses, as their thermoregulation is largely dependent on the mother. However, the few studies which addressed fetal yawning are often plagued by serious methodological issues, in particular concerning the validity and reliability of methods adopted to identify yawns, resulting in contradictory results. In the present study, we scored yawns and other mouth openings in 32 healthy fetuses observed during ultrasonographic scans between the 23rd and the 31st gestational week, using the Baby FACS-based System for Coding Perinatal Behavior (SCPB). We found average yawning frequencies to be below 5 per hour, and not related with gestational age (GA). Non-yawning mouth openings, instead, showed a GA-related decrease that, together with validity issues of measurement methods, might explain the similar developmental trend found for yawning frequencies in two previous studies. Finally, yawning frequencies were negatively related with birth weight, considered as an indicator of mild distress, potentially showing a stress-related modulation of yawning behavior in healthy fetuses.